การวิเคราะห์แนวคิดเรื่องการเรียนรู้ตลอดชีวิตเพื่อการพัฒนาที่ยั่งยืนของ พระพรหมคุณาภรณ์ (ป.อ. ปยุตฺโต) - ชาคริต อาชวอำรุง (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this study were: 1) to study, compile and analyze Phrabrahmgunabhorn (P.A. Payutto)’s approaches to life-long learning for sustainable development regarding ideas, form of education, process and support. 2) to propose guidelines for organizing life-long learning for sustainable development regarding target groups, organizers and process according to his approaches. This study was a qualitative research using documentary research and interviews. The study was validated by an expert. The research findings were as follows: 1. The idea of Phrabrahmgunabhorn (P.A. Payutto) of life-long learning for sustainable development is that sustainable development will occur when people are developed according to Sikkhā (Threefold learning) that will lead to individuals, society and environment live together in balance and harmony. His idea on forms of study is that all forms of study consist of teachers and learners. The roles of teachers are not only to teach knowledge and skills but also to teach how to live a good and moral life. The process of learning is when humans perceive stimulus through their senses and use them as information to improve quality of life in all areas and there are many factors that encourage this process. The ways to promote live-long learning are to promote those factors. 2. For target groups, Phrabrahmgunabhorn (P.A. Payutto) gives guidelines for people in general with emphasis on children. Parents, teachers, government and society, educational institutions as well as medias are regarded as organizers of life-long learning. The proposed process that will facilitate life-long learning is to develop Chanda (zeal for learning), encourage educational activities and instill discipline and the love of nature.